Progress in procedural justice: tunnelling through the maze - Jahangir, Nadim; Haq, Mahmudul; Ahmed, Ezaz (BRAC University, 2010)
Recent developments in the contribution to the literature on procedural justice have opened avenues for exploring the subject and gaining perspective in the field with a view to assessing how the concept of procedural justice has evolved over the periods and how it is shaping up for the future. This paper reviews the procedural justice literature since 1990. Four theories exploring procedural justice are presented. The antecedents, consequences, and contexts for procedural justice effects are reviewed. This study reveals that attention to matters relating to procedural justice need to be practiced in the foreseeable future.